"If the Library Genie Granted You Three Wishes, What Would They Be?": Results and Lessons Learned From an Annual User Feedback Campaign. Issue 1 (2nd January 2017) - De Santis, Melissa; Houghton, Vivienne; Fontenelle, Cathalina
ABSTRACT: The Health Sciences Library at the University of Colorado Anschutz Medical Campus implemented a user feedback campaign that successfully provided input about user needs. The library created an engaging marketing theme and employed a simple form to successfully solicit feedback from users. The program has been easy to replicate in subsequent years, and other health sciences libraries have been able to recreate the process at their institutions.